GLOBAL LINKS, LOCAL THREATS: THE IMPACT OF INTERNATIONAL TERRORISM NETWORKS ON DOMESTIC TERRORISM IN MALAYSIA - Haron, Zulkarnain; Abdul Rahman, Shaharudin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This research examines the impact of international terrorist networks on domestic terrorism in Malaysia, with a focus on groups such as Al-Qaeda, ISIS @ Daesh, Al Jamaah Al Islamiyah (JI), Jamaah Ansharut Daulah (JAD) and Abu Sayyaf. Using a qualitative, case-based method, this paper explores how recruitment, radicalisation and financing processes connect global jihadist movements to Malaysian extremist actors. Recruitment is often facilitated through encrypted platforms and social media, supported by transnational links with Indonesian and Filipino militants. Marginalised and uneducated populations, including Rohingya refugees and Southern Thai communities, are particularly vulnerable due to socio-political and economic hardships. Radicalisation is driven by extremist content in Bahasa Malaysia and Indonesian languages, spread through online media and jihadist publications. Returning foreign fighters from Syria and Iraq further deepen the threat, bringing combat experience and hardened ideologies that can strengthen local networks. Terrorism financing in Malaysia relies on informal mechanisms such as hawala, misuse of charitable organisations and the increasing use of cryptocurrencies. Authorities have exposed several cases involving NGOs and individuals accused of funding foreign terrorist groups under humanitarian cover. The study underscores the need for stronger regional and international cooperation, highlighting Malaysia’s role in trilateral patrols, ASEAN intelligence exchanges and global counterterrorism partnerships. This paper concludes that an integrated strategy combining intelligence sharing, legal enhancements and community resilience is critical to disrupt the evolving nexus between terror networks and domestic security threats in Malaysia.